2015
DOI: 10.3389/fgene.2015.00271
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of circulating transfer RNA-derived RNA fragments in cattle

Abstract: The objective was to characterize naturally occurring circulating transfer RNA-derived RNA fragments (tRFs) in cattle1. Serum from eight clinically normal adult dairy cows was collected, and small non-coding RNAs were extracted immediately after collection and sequenced by Illumina MiSeq. Sequences aligned to transfer RNA (tRNA) genes or their flanking sequences were characterized. Sequences aligned to the beginning of 5′ end of the mature tRNA were classified as tRF5; those aligned to the 3′ end of mature tRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 18 publications
5
23
0
Order By: Relevance
“…Altogether, 5p-derived fragments represented 63% of all bull sperm tsRNAs, with tRF3s and 3p-tRHs being expressed at low levels (30× less expressed than 5p derived fragments). A similar pattern was also described in bull sera [59], but with a larger contrast, where 5p-derived fragments were 4000× more expressed than 3p ones. This discrepancy may be related to biological differences between tissues, as suggested by the extensive differences in tRF expression observed between human biofluids [60].…”
Section: The Overall Small Rna Content Of Bull Spermsupporting
confidence: 79%
“…Altogether, 5p-derived fragments represented 63% of all bull sperm tsRNAs, with tRF3s and 3p-tRHs being expressed at low levels (30× less expressed than 5p derived fragments). A similar pattern was also described in bull sera [59], but with a larger contrast, where 5p-derived fragments were 4000× more expressed than 3p ones. This discrepancy may be related to biological differences between tissues, as suggested by the extensive differences in tRF expression observed between human biofluids [60].…”
Section: The Overall Small Rna Content Of Bull Spermsupporting
confidence: 79%
“…tiRNA-5, tiRNA-3, tRF-3, tRF-5, and i-tRF series which are generated from mature tRNAs constituted the majority in our samples, whereas the tRFs (tRF-1) generated from the primary tRNAs were in the minority. This phenomenon is consistent with previous reports (Casas et al 2015;Olvedy et al 2016;Wei et al 2012).…”
Section: Discussionsupporting
confidence: 94%
“…Then, tRFs were detected in other kinds of human cells or tissues (Zhou et al 2017;Yeung et al 2009;Wang et al 2013). tRFs were also evaluated in plants or other animals, such as barley (Hackenberg et al 2013) and cattle (Casas et al 2015). Given their widespread presence, the tRFs are expected to play key roles in many physiological and pathological processes.…”
Section: Discussionmentioning
confidence: 99%
“…These tRFs were originally viewed as tRNA degradation products often found in next generation sequencing (NGS) data sets, however, the recurrence of reads matching specific domains of mature tRNAs, rather than random alignment throughout mature tRNA primary structures strongly suggested that these sncRNAs could be functional . tRFs were also uncovered in a panoply of organisms and their biogenesis was found to be dependent on cell type, physiological conditions, and developmental stages, suggesting high level conservation and specific tRNA cleavage rather than random tRNA degradation. Initial studies also showed that tRFs were a heterogeneous class of sncRNAs with different sizes that could originate from either the pre‐ or mature tRNA molecule .…”
Section: Introductionmentioning
confidence: 99%